Hygroscopic properties of NaCl nanoparticles on the surface: a scanning force microscopy study. Issue 18 (30th April 2020) - Wang, Xiaoxiang; Lei, Haozhi; Berger, Rüdiger; Zhang, Yi; Su, Hang; Cheng, Yafang
Abstract : We investigated the hygroscopic growth of sodium chloride (NaCl) nanoparticles with curvature related diameters ranging from 10 nm to 200 nm, at different relative humidities using scanning force microscopy. Abstract : We investigated the hygroscopic growth of sodium chloride (NaCl) nanoparticles with curvature related diameters ranging from 10 nm to 200 nm, at different relative humidities using scanning force microscopy. Hygroscopic aerosol nanoparticles play a vital role in the Earth's climate and human health. We report that 10 nm NaCl nanoparticles adsorbed on silicon surfaces have a higher deliquescence relative humidity than larger NaCl nanoparticles (size > 30 nm). This finding is consistent with the observations for airborne nanoparticles by hygroscopicity tandem differential mobility analyzer. Therefore, the presence of silicon surfaces plays no significant role in the deliquescence relative humidity. Moreover, the study of individual airborne particles by means of scanning force microscopy revealed that the ability of water uptake, i.e. growth factor, of NaCl particles differs by as large as 40% at the same relative humidity. This finding indicates that the individual nature of NaCl particles influences the growth factor.